Mesin Pengupas Bawang Mudah – Alih (Portable Onion Peeler Machine) - Sahrudin Sahrudin; Dimas Ramadhan Putra; Jhav Sund Oktoricoento; Mohammad Mujirudin; Harry Ramza (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2018)
The process of processing agricultural products into a food for the community becomes an interesting thing to know more deeply. One of them is pengelolahan onion with a lot of capacity for stripping process. In the process of onion processing there are several obstacles that make its production to inhibit one of them is in stripping the skin of onion and garlic by means of chopped to peel it. The producers often find it difficult to clean the onion skin at the time of stripping, let alone a large degree. The design of this tool is made to assist in the process of stripping the onion in large quantities using electric motor power as the driving force, the microcontroller as the brain to run the process of designed devices and load sensors to calculate the value of the weight capacity of the onion. The ties cable serves as a helper in stripping onions by banging them. With the aim of Determining the value of the efficiency of the thickness of the peel skin and the weight capacity of the onion, so that the best variation to be used is the variation of the combination with a value of efficiency of 17% for thickness and 3% for the weight capacity of the onion.